2023
DOI: 10.3390/antiox12030724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Size of Curcumin Solid Dispersions on Bioavailability and Anti-Inflammatory Activities

Abstract: The delivery of curcumin (CUR) using the solid dispersion system (CUR solid dispersions; C-SDs) has been shown to improve CUR bioavailability. However, it is unclear how different particle sizes of C-SDs affect the bioavailability and biological activities of CUR. Hence, we prepared C-SDs in different sizes using food-grade excipients and evaluated their bioavailability and biological activities. By pulverizing large particle sizes of C-SDs using zirconia beads, we successfully prepared C-SDs I-IV (particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…A review of 11 curcumin nanoformulations tested in clinical studies showed increased relative bioavailability (RB) ranging from 9- to 185-fold, but an analysis of the design of these studies, curcumin dosage, administration, analytical method, pharmacokinetic parameters, and the composition of study population revealed differences that make it difficult to compare these RB numbers directly [ 52 ]. Not only the composition of nanoparticles affects the bioavailability, but also particle size and route of administration [ 53 ], e.g., for curcumin prepared as solid dispersions, a smaller particle size increased the bioavailability when administered orally, whereas a larger particle size increased the bioavailability when administered intravenously [ 54 ].…”
Section: Curcumin and Curcuminoidsmentioning
confidence: 99%
“…A review of 11 curcumin nanoformulations tested in clinical studies showed increased relative bioavailability (RB) ranging from 9- to 185-fold, but an analysis of the design of these studies, curcumin dosage, administration, analytical method, pharmacokinetic parameters, and the composition of study population revealed differences that make it difficult to compare these RB numbers directly [ 52 ]. Not only the composition of nanoparticles affects the bioavailability, but also particle size and route of administration [ 53 ], e.g., for curcumin prepared as solid dispersions, a smaller particle size increased the bioavailability when administered orally, whereas a larger particle size increased the bioavailability when administered intravenously [ 54 ].…”
Section: Curcumin and Curcuminoidsmentioning
confidence: 99%
“…Studies have indicated that curcumin inhibits various inflammatory pathways, including lipo-oxygenase and cyclo-oxygenase activities, nitric oxide production and ROS generation in different cell types (Hatcher et al, 2008). Kato et al (2023) investigated the anti-inflammatory activities of curcumin solid dispersions (C-SDs) in rats. They observed that smaller particle sizes of C-SDs were associated with increased bioavailability and anti-inflammatory effects.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%